Social capital, firm performance, operating business environment - Salome Kanini Kaberia; Stephen Muathe; Hannah Bula (The Journal of Entrepreneurial Finance (JEF), 2022)
Globally, manufacturing sector is recognized as a key driver of economic development. Kenya's manufacturing sector has been no exception; with a contribution of 10% to gross domestic product for the duration 2008 to 2014. However, records reveal that in 2017, 2018 and 2019, the contribution deteriorated to 8.4%, 7.7% and 7.54% respectively, suggesting a possible premature de-industrialization. Should this trend persist, Kenya's goal of achieving a robust manufacturing sector through the Big Four Agenda may not be achieved. While the government has implemented strategies and interventions to boost the sector, these do not seem to reverse the trend. It is against this backdrop that the study sought to explore how social capital as a readily available resource can be tapped to enhance performance among the micro, small and medium manufacturing enterprises. The study objective was to determine to what extent social capital influenced firm performance among micro, small and medium manufacturing enterprises, considering the moderating role of business operating environment. The study used relevant theories namely social capital theory, resource-based view, and dynamic capability, among others. 384 ventures were sampled from a population of 61,931 licensed manufacturing businesses operating within Nairobi City County. Primary data was collected through questionnaires and analyzed using descriptive and inferential statistics. Findings indicated that social capital positively and significantly predicted performance of micro, small and medium manufacturing enterprises. No moderating effect was found in the link between social capital, operating environment and performance. The study recommends that management and policy interventions harness more and diverse networks to enable firms better manage changes within the operating environment without adverse impact on performance.
Keywords: 650; Social Capital; Firm Performance; Operating Business Environment